Experiences of living with symptomatic atrial fibrillation - Lena Holmlund; Karin Hellström Ängerud; Åsa Hörnsten; Fredrik Valham; Karin Olsson (Wiley, 2023)
Abstract Aim To explore the experiences of living with symptomatic atrial fibrillation. Design This study, with a descriptive qualitative design, was performed using semi‐structured individual interviews. Method Six women and nine men with symptomatic atrial fibrillation were included. The transcribed interviews were analysed using qualitative content analysis. The COREQ checklist was followed. Results The analysis resulted in a main theme, namely balancing life and included the themes striving for illness control, becoming a receiver or an active partner in care and dealing with changed self‐image. The participants strived to understand their illness, prevent attacks and manage anxiety. Some of the participants were not involved in decision‐making, were uninformed about self‐care measures, reported a lack of continuity in care and felt that the doctors focused on information about the medical part of care.